Wildlife and Livelihoods in the Cardamom Mountains, Cambodia - Coad, L.M.; Lim, S.; Nuon, L. (Frontiers Media, 2019)
This study provides a preliminary assessment of the use of wild meat and fish by rural communities in the Northern Cardamoms, Cambodia. We used a case-study approach in three villages, to identify key characteristics and drivers of wildlife use, with a view to informing the design of future larger-scale investigations of wild meat and fish use in the Cardamoms. Interviews with 41 households, conducted from August - October 2013, were used to investigate the main livelihood activities of each household, including hunting and fishing activity, key hunting techniques and hunted and consumed species. Group discussions with households and hunters were used to determine the relative importance of hunting and fishing as a livelihood activity and food source. We found that over 80% of interviewed households hunted, and similarly over 90% fished. Hunters employed a range of techniques, and caught at least 38 different mammal, bird and reptile species. However, our results suggest that arable farming is the backbone of livelihoods in these villages, providing the bulk of household incomes, and that most households are hunting to prevent crop-raiding, or opportunistically, rather than to supply the commercial trade. While households expressed a preference for wild meat, bought domestic meats and fish were eaten more frequently. A potentially lucrative commercial trade with high profits per animal exists but catches are unpredictable, and hunting is dangerous. However, as many species populations are already heavily depleted, even low hunting offtakes could have significant impacts on vulnerable species. Previous research suggests that commercial hunting which targets larger-bodied and high-value species for the international wildlife trade is mainly conducted by professional hunting groups, external to local communities. The importance of agricultural trade to local communities suggests that 'wildlife-friendly farming' initiatives may help to both secure a fair and reliable price for village agricultural products, while promoting conservation of biodiversity in the Cardamoms mountains. However, due to the likely larger impacts of commercial hunting groups, declines in biodiversity are likely to continue without stricter enforcement of wildlife trade laws in Cambodia's towns and cities, and the reduction of demand for wildlife products in consumer countries.